Association of cardiorespiratory fitness with phenotypic age in younger population: a study based on the NHANES database - Yi Shen; Wanying Shen; Yongyao Shen; Bo Chen; Cui Wu; Liying Jiang; Liying Jiang (Frontiers in Sports and Active Living)
BackgroundPhenotypic age (PA), a novel signature of morbidity and mortality risk based on clinically collected parameters, is considered one of the most promising biomarkers for capturing aging. However, unequivocal evidence on the link between cardiorespiratory fitness (CRF), assessed by estimated maximal oxygen consumption (Vo2max), and PA remains scarce, particularly within the first half of life. This study aims to explore the relationships between CRF and the age-adjusted value derived from the residuals of the regression of PA on chronological age (PhenoageAcceleration: PAA), uncovering the prognostic value of CRF in the early lifetime to provide perspectives for understanding and improving healthy aging.MethodsData from 3,069 participants in the National Health and Nutrition Examination Survey (NHANES) were included and further examined. CRF status was determined by Vo2max according to gender and age-specific criteria, with low and moderate levels classified as impaired CRF. PA was calculated from multisystem blood biomarkers and chronological age. The association of CRF status with cross-sectional PAA was investigated, and subgroup analyses were further performed to explore and identify potentially vulnerable populations.ResultsIn the multivariable logistical regression analysis, maintenance of CRF was significantly and inversely associated with PAA, demonstrating a decreased risk of 42% in the high CRF group [OR (95% CI): 0.58 (0.36, 0.96), p = 0.033]. Compared with those with non-impaired CRF, those in the impaired group exhibited a rise in PA by 1.46 years [β (95% CI): 1.46 (1.03, 2.10), p = 0.040]. Interestingly, in the population of over 29 years’ old, a significant interaction between obesity and impaired CRF for PAA was observed (p = 0.018; p = 0.026).ConclusionsPoor CRF may serve as a potential risk factor for accelerated biological aging (BA) in relatively young populations, and the existence of obesity could exacerbate the aging process. This represents a potential intervention target for promoting healthy aging across different age groups in the future.